Effects of EPS Beads on the Unconfined Compressive Strength and Stiffness of Bentonite Soil-Cement Mixture - Lim, Aswin; Pratama, Ignatius Tommy; Verguson, Yoghi Jo (Universitas Negeri Semarang, 2023)
Expanded Polystyrene Beads (EPS Beads) have characteristics that are lightweight and low density. However, EPS is waste that does not pollute the soil, but has hundreds of years to decompose, thereby reducing the landfill area. Therefore, alternative disposal is to use EPS for soil improvement. The effects of different EPS beads size on the mechanical behavior of bentonite soil-cement mixture were studied using the unconfined compression test. The curing time of the mixture also varied from 7 to 28 days. The results indicate that adding EPS beads to the soil-EPS beads-cement mixture changed the behavior of the material to be more ductile. The samples could also support larger stresses at a lower strain level, less than 1 %. Furthermore, the unconfined compressive strength of the mixture of bentonite, EPS, and cement increased with increasing curing time and decreased with increasing EPS beads size. Then, adding EPS beads to the soil-cement mixture regardless of its size also promoted a larger stiffness of the samples compared to the sample with no EPS beads in the mixture.